Interferensi Morfologi dan Sintaksis Bahasa Indonesia Terhadap Bahasa Arab: Studi Analisis Pada Siswi Kelas IX MTs Riyadlotut Thalabah Sedan Rembang Tahun Ajaran 2023/2024 - Diana Nahdliatin Nur; Ushie Uswatun Hasanah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to: 1) identify the forms of errors in Arabic language, specifically morphological and syntactic interference, experienced by the ninth-grade female students of MTS Riyadlotut Thalabah Sedan Rembang; 2) explore the factors causing these interference errors; and 3) determine the efforts to minimize these errors by the teacher. The research is a descriptive qualitative field study conducted at MTS Riyadlotut Thalabah with a sample of 40 ninth-grade students. Data collection methods include observation, interviews, and documentation, with qualitative analysis applied to the data. The findings show that interference errors occurred in two main areas: morphology and syntax. Morphological errors include mistakes in conjugation and word choice, while syntactic errors involve issues with agreement, i'rab, pronoun usage, and the application of conjunctions. The causes of these errors are classified into three factors: interlingual, intralingual, and performance-related. To minimize these errors, teachers should focus on increasing the practical application of the Arabic theories learned.